A Concise Route to the Strongylophorines. Issue 29 (30th May 2016) - Yu, Wanwan; Hjerrild, Per; Overgaard, Jacob; Poulsen, Thomas B.
Abstract: An efficient eight‐step semisynthesis of strongylophorine‐2 from the abundant building block isocupressic acid is reported. The route represents the first synthetic entry into this class of natural products and provides access to six additional family members. A novel iron(III)‐mediated rearrangement–cyclization cascade and a directed photochemical sp 3 C−H δ ‐lactonization are the key transformations that enable concise assembly of these bioactive polycyclic meroterpenoids. Abstract : No detours : A powerful semisynthetic strategy to meroterpenoids of the strongylophorine (STR) family is reported. Starting from the abundant sesquiterpene isocupressic acid, a new Lewis acid mediated allylic rearrangement–cyclization cascade and a strategic methyl C−H activation reaction enabled expedient construction of seven members of the STR family, including STR‐2.